Introducing the medieval swan. - Goodison, Natalie Jayne (Cardiff : University of Wales Press, 2022)
This book examines the swan in medieval literature, spanning from Classical to Early Modern associations.
Cover -- Title Page -- Copyright Page -- Series Editors' Preface -- Contents -- Acknowledgements -- List of Plates and illustrations -- List of Abbreviations -- Introduction -- 1 The Swan in Natural History:The Swan's Song -- 2 The Swan in Literature:Transformation of Men, Women, and Children -- 3 The Swan at Court:The Descendants of the Swan Knight -- 4 The Swan in Practice:Cookery, Husbandry, and the Law -- 5 Swansong:The Afterlives of the Medieval Swan -- Endnotes -- Bibliography -- Primary -- Secondary -- Websites/News Articles -- Online Sources for Images -- Objects -- Index
Includes bibliographical references.
eBooks on EBSCOhost
Keywords: English literature -- Middle English, 1100-1500 -- History and criticism; Swans in literature; Littérature anglaise -- 1100-1500 (Moyen anglais) -- Histoire et critique; HISTORY / Europe / Medieval; English literature -- Middle English; Swans in literature; 1100-1500; Criticism, interpretation, etc; Literary criticism; Critiques littéraires.